Emerging nitric oxide gas‐assisted cancer photothermal treatment - Shuang Liang; Yufei Liu; Hongquan Zhu; Guangfu Liao; Wenzhen Zhu; Li Zhang (Exploration)
Abstract Photothermal therapy (PTT) has garnered significant attention in recent years, but the standalone application of PTT still faces limitations that hinder its ability to achieve optimal therapeutic outcomes. Nitric oxide (NO), being one of the most extensively studied gaseous molecules, presents itself as a promising complementary candidate for PTT. In response, various nanosystems have been developed to enable the simultaneous utilization of PTT and NO‐mediated gas therapy (GT), with the integration of photothermal agents (PTAs) and thermally‐sensitive NO donors being the prevailing approach. This combination seeks to leverage the synergistic effects of PTT and GT while mitigating the potential risks associated with gas toxicity through the use of a single laser irradiation. Furthermore, additional internal or external stimuli have been employed to trigger NO release when combined with different types of PTAs, thereby further enhancing therapeutic efficacy. This comprehensive review aims to summarize recent advancements in NO gas‐assisted cancer photothermal treatment. It commences by providing an overview of various types of NO donors and precursors, including those sensitive to photothermal, light, ultrasound, reactive oxygen species, and glutathione. These NO donors and precursors are discussed in the context of dual‐modal PTT/GT. Subsequently, the incorporation of other treatment modalities such as chemotherapy (CHT), photodynamic therapy (PDT), alkyl radical therapy, radiation therapy, and immunotherapy (IT) in the creation of triple‐modal therapeutic nanoplatforms is presented. The review further explores tetra‐modal therapies, such as PTT/GT/CHT/PDT, PTT/GT/CHT/chemodynamic therapy (CDT), PTT/GT/PDT/IT, PTT/GT/starvation therapy (ST)/IT, PTT/GT/Ca2+ overload/IT, PTT/GT/ferroptosis (FT)/IT, and PTT/GT/CDT/IT. Finally, potential challenges and future perspectives concerning these novel paradigms are discussed. This comprehensive review is anticipated to serve as a valuable resource for future studies focused on the development of innovative photothermal/NO‐based cancer nanotheranostics.